DOES FOREIGN OWNERSHIP MATTER IN THE RELATIONSHIP BETWEEN FIRM SIZE AND CARBON EMISSION DISCLOSURE? - Santoso, Arif; Kurniasari, Ratri; Ginting, Riskon; Permananingrum, Adilah; Barry, Husnil (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
As the issue of climate change escalates, carbon emissions have become a growing concern for stakeholders. Carbon emission disclosure (EMISSION) is no longer an option for companies seeking legitimacy, but rather a strategic necessity to ensure corporate sustainability. This study aims to examine the relationship between firm size (FSIZE), foreign ownership (FOROWN), and EMISSION. The study was conducted on energy sector companies in Indonesia during the period 2019-2022. The final sample of this study was 225 observations units and was analyzed using Moderated Regression Analysis (MRA) in STATA 16. This study found that FSIZE has a positive and significant effect on EMISSION. FOROWN shows an important role in strengthening the relationship between FSIZE and EMISSION. The role is more pronounced in smaller firms, where stakeholder monitoring and attention may be weaker. This finding supports Stakeholder Theory and has been confirmed through sub-sample analysis, quantile regression, and coarsened exact matching (CEM). The findings confirm that larger companies, especially those backed by foreign investors, can act as a force for good in encouraging environmental transparency practices and responding to stakeholder demands. In addition, this study also offers unique empirical and practical insights in the corporate social responsibility (CSR) literature.